Reflections on the policy-practice gap: Adaptive interpretation of curriculum levels by Indonesian EFL teachers - Kalayo Hasibuan; Siti Fadilah Sukma; Dinda Kurniawati; Dinda Salsa Bella (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Curriculum reform in Indonesia, notably the Merdeka Curriculum, has introduced explicit language proficiency levels benchmarked against the Common European Framework of Reference for Languages (CEFR). This article undertakes a critical narrative literature review to analyze how English as a Foreign Language (EFL) teachers in Indonesian contexts interpret and implement these policy-mandated curriculum levels. Findings demonstrate a significant policy-to-practice gap, primarily characterized by high conceptual inconsistency regarding CEFR descriptors and a compulsory process of contextual adaptation necessary due to profound classroom constraints. The analysis reveals three systemic deficits: insufficient, non-contextualized professional development (PD); scarcity of resources compounded by teacher competency gaps; and an inherent tension between mandated policy fidelity and professional pedagogical autonomy. The article concludes that teacher interpretation constitutes a vital, non-linear adaptive professional mechanism that translates abstract policy into locally relevant pedagogy. This necessitates that future policy design formally recognizes and empower this essential teacher agency to ensure sustainable and equitable curriculum implementation.